2022
DOI: 10.1186/s12955-022-01963-5
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and validation of the HIV Knowledge Questionnaire-18 for the general population of Indonesia

Abstract: Background Despite a global decline in new HIV/AIDS cases in low-middle countries, cases are increasing in Indonesia. Low knowledge about the disease among the general population is one of the major factors responsible for this trend. Indonesia does not have a validated instrument to assess HIV/AIDS knowledge. The HIV Knowledge Questionnaire-18 (HIV-KQ-18) has been translated into several languages and is one of the most extensively used instruments for assessing HIV/AIDS knowledge. This paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In total, there were 5,364 participants in this study. This number of participants was almost 5 times higher than the number of participants in the Indonesian adaptation and validation study of the HIV-KQ-18 instrument [11]. The socio-demographic characteristics revealed that about 60% of the participants were between the ages of 17 and 25.…”
Section: Participant Characteristicsmentioning
confidence: 75%
See 3 more Smart Citations
“…In total, there were 5,364 participants in this study. This number of participants was almost 5 times higher than the number of participants in the Indonesian adaptation and validation study of the HIV-KQ-18 instrument [11]. The socio-demographic characteristics revealed that about 60% of the participants were between the ages of 17 and 25.…”
Section: Participant Characteristicsmentioning
confidence: 75%
“…For participants who answered 'don't know, a score of 0 was also counted. This instrument has been validated into Bahasa Indonesia and has passed the "cross cultural adaption" test [11]. Notably, Prof. Michael P. Carey, Ph.D., has given his approval for the license to use this instrument (via email on February 11, 2020).…”
Section: Instrumentmentioning
confidence: 99%
See 2 more Smart Citations
“…The study began by contacting the developer of the HIV-KQ-18, Professor Michael P. Carey and he has given permission and expressed support for the validation testing of the same instrument for the Indonesian general population (Arifin et al, 2022). Therefore, this study was a part of larger study by (Arifin et al, 2022), although this study's focus was solely on D.I Yogyakarta (Yogyakarta Province). The fact that the two studies' data collecting was undertaken concurrently should be noted (but the respondents and the databases were also different).…”
Section: Research Processmentioning
confidence: 99%